Developing Pragmatic Competence in Iranian EFL Classrooms - Abdulhay, Husain (International Journal For Research In Educational Studies, 2016)
The study sought to discern how the explicit teaching of the speech acts of opening and closing conversations facilitated by teacher influences the performances of Iranian EFL learners. Four activities were incorporated into the set program: translating a conversation from Persian into English, developing the conversation and in the end doing the role play. Participants were divided into a treatment and a control group (32 and 13) respectively and their performances were measured by a pre- and a post-test requiring the students to perform a dialog with their peers to score the presence and appropriateness of opening and closing and elaborating them according to situations in their tasks. The findings yielded that treatment group utilized more elaborate opening and closing elements. The results support and extend prior research on the effectiveness of classroom-based instruction for EFL learners’ pragmatic development.